Litoral Urbanização Ambientes e seus Ecossistemas Frágeis - Macedo, Silvio Soares (Paisagem e Ambiente, 1999)
The urbanization in the Brazilian coastal zone had been the main factor of destruction of their ecosystens as m angroves, coral reefs, dunes and restinga's forests. This paper focuse their effects over these ecosystens and explain how to avoid them